2019
DOI: 10.1111/zph.12611
|View full text |Cite
|
Sign up to set email alerts
|

Infection, colonization and shedding of Campylobacter and Salmonella in animals and their contribution to human disease: A review

Abstract: Livestock meat and offal contribute significantly to human nutrition as sources of high‐quality protein and micronutrients. Livestock products are increasingly in demand, particularly in low‐ and middle‐income settings where economies are growing and meat is increasingly seen as an affordable and desirable food item. Demand is also driving intensification of livestock keeping and processing. An unintended consequence of intensification is increased exposure to zoonotic agents, and a contemporary emerging probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 205 publications
(293 reference statements)
3
51
0
1
Order By: Relevance
“…Our analysis of BEV proteins under different culture conditions highlights the ability of Bt to effectively respond to nutrient stress by changing the profile of proteins it produces and packages in its BEVS, as predicted in a prior transcriptomics based study [29]. A similar phenomenon has been described in Campylobacter jejuni, which, although considered to be a commensal bacterium in avian hosts, is pathogenic and causes bacterial gastroenteritis in humans [46]. Proteomic analysis of the C. jejuni BEVs identified numerous proteins with differential abundance under culture conditions reflecting the different body temperatures of the two hosts, with significantly higher amounts of virulence proteins associated with BEVs from cultures at 37 • C culture compared to BEVs produced at 42°C [47].…”
Section: Discussionsupporting
confidence: 59%
“…Our analysis of BEV proteins under different culture conditions highlights the ability of Bt to effectively respond to nutrient stress by changing the profile of proteins it produces and packages in its BEVS, as predicted in a prior transcriptomics based study [29]. A similar phenomenon has been described in Campylobacter jejuni, which, although considered to be a commensal bacterium in avian hosts, is pathogenic and causes bacterial gastroenteritis in humans [46]. Proteomic analysis of the C. jejuni BEVs identified numerous proteins with differential abundance under culture conditions reflecting the different body temperatures of the two hosts, with significantly higher amounts of virulence proteins associated with BEVs from cultures at 37 • C culture compared to BEVs produced at 42°C [47].…”
Section: Discussionsupporting
confidence: 59%
“…An estimate of 80-90% of poultry flocks are colonized mainly with C. jejuni; the rest are colonized with C. coli or, infrequently, with Campylobacter lari [3][4][5]. Although consumption of undercooked Campylobacter-contaminated poultry or mishandling of raw poultry products was documented by different studies as the most important infection sources worldwide [6,7], a different recent observational studies identified other potential sources as ruminants (cattle and sheep), dogs, cats, pigs, and the environment [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…With the acceleration of economic globalization and trade liberalization, food safety has been a global public health issue prompting widespread concern [1]. Salmonella is an important food-borne pathogen causing food poisoning, which can transmit along the food production chain from farm to an retail chain, leading to severe foodborne diseases [2][3][4]. Salmonella is widespread in the natural environment, and can grow under ambient temperature conditions.…”
Section: Introductionmentioning
confidence: 99%